(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The per capita accessibility of water is diminishing step by step because of increment in populace. The accessible water resources are additionally getting dirtied with modern, agrarian and residential effluents, and this, thus, is further constraining the accessibility of usable water resources.